Genetic variability for fodder quality traits among high biomass energy cane feedstock under rainfed conditions - Meena, Mintu Ram; Perumal, Govindaraj; Meena, Rajesh Kumar; Raja, Arun Kumar; Kumar, Ravinder; Chhabra, M L; Pandey, S K Pandey; Govind, G. Hemaprabha (Journal of Sugarcane Research, 2023)
Eighteen energy canes (Types I and II) were evaluated along with two popular varieties Co 0238 and CoS 767 under rainfed conditions of sub-tropical climate for their potential as fodder crop. The analysis of fodder quality parameters at the 10 month crop stage included crude protein content, dry matter intake (DMI), dry matter digestibility %, total digestible nutrients %, net energy of lactation, and digestible ﬁbre and energy. Sugarcane tops of type-I and type-II energy canes had similar crude protein percentages (5.95 % and 6.61 %). Energy canes; SBIEC 14002, SBIEC 11009, SBIEC 11003, SBIEC 13009, and SBIEC 11006 recorded dry matter intake % of 1.76%, 1.76%, 1.73% and 1.72%, 1.70% respectively, which was on par with sugarcane (1.71%). The digestible nutrient of SBIEC 11001 (49.43%) was higher than that of cultivated canes, whereas that of SBIEC 11009 (48.08%), SBIEC 11005 (48.64%) and SBIEC 14003 (48.50%) was similar to that of cultivated canes. The correlation coefficient between desirable fodder traits was calculated. A highly positive correlation (r=1.0) was observed among the ﬁve desirable traits, such as net available energy, metabolisable energy, dry matter digestibility, total digestible nutrient, and digestible energy, indicated there desirability for fodder value. Based on their traits, two-way cluster analysis separated Type-I and Type-II energy clones into two major groups. According to all parameters considered, energy-cane tops had acceptable fodder quality and were on par with cultivated sugarcane varieties.